Pengembangan Aplikasi Toko Buku berbasis Web (Studi Kasus: Toko Buku Online Yukmoco) - Bregaster Bregaster; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Yukmoco is a bookstore domiciled in the city of Surabaya. Yukmoco sells products indirectly through various warehouse partners. Yukmoco stores its products in multiple cities according to where the warehouse partners are located. The business process carried out by Yukmoco still has several problems. Among this problem is that the system currently owned by Yukmoco can only make purchases at one warehouse partner in one transaction. Another problem that occurs is the need to monitor orders placed by buyers. The web-based E-Commerce system was developed to solve existing problems. System development is carried out using the waterfall model, which uses an object-oriented approach. The system was developed with the PHP programming language using the Laravel framework, and the database used is a relational database using MySQL. The developed system has been tested using unit testing on the 3 main methods of the system with valid results. Integration testing is carried out on 2 related methods to produce valid test results. Validation testing was carried out on 22 functional requirements to have valid results. Compatibility testing states that the system can run well on 5 popular web browsers. The results of usability testing with the SUS method obtained a result of 79, which means the system is acceptable to users.